IFNγ mediates the resistance of tumor cells to distinct NK cell subsets - Hofman, Tomáš; Ng, Siu Wang; Garcés Lázaro, Irene; Heigwer, Florian; Boutros, Michael; Cerwenka, Adelheid (Journal for ImmunoTherapy of Cancer, 2024)
Background Immune checkpoint blockade targeting the adaptive immune system has revolutionized the treatment of cancer. Despite impressive clinical benefits observed, patient subgroups remain non-responsive underscoring the necessity for combinational therapies harnessing additional immune cells. Natural killer (NK) cells are emerging tools for cancer therapy. However, only subpopulations of NK cells that are differentially controlled by inhibitory receptors exert reactivity against particular cancer types. How to leverage the complete anti-tumor potential of all NK cell subsets without favoring the emergence of NK cell-resistant tumor cells remains unresolved. - Methods We performed a genome-wide CRISPR/Cas9 knockout resistance screen in melanoma cells in co-cultures with human primary NK cells. We comprehensively evaluated factors regulating tumor resistance and susceptibility by focusing on NK cell subsets in an allogenic setting. Moreover, we tested therapeutic blocking antibodies currently used in clinical trials. - Results Melanoma cells deficient in antigen-presenting or the IFNγ-signaling pathways were depleted in remaining NK cell-co-cultured melanoma cells and displayed enhanced sensitivity to NK cells. Treatment with IFNγ induced potent resistance of melanoma cells to resting, IL-2-cultured and ADCC-activated NK cells that depended on B2M required for the expression of both classical and non-classical MHC-I. IFNγ-induced expression of HLA-E mediated the resistance of melanoma cells to the NKG2A+ KIR− and partially to the NKG2A+ KIR+ NK cell subset. The expression of classical MHC-I by itself was sufficient for the inhibition of the NKG2A− KIR+, but not the NKG2A+ KIR+ NK cell subset. Treatment of NK cells with monalizumab, an NKG2A blocking mAb, enhanced the reactivity of a corresponding subset of NK cells. The combination of monalizumab with lirilumab, blocking KIR2 receptors, together with DX9, blocking KIR3DL1, was required to restore cytotoxicity of all NK cell subsets against IFNγ-induced resistant tumor cells in melanoma and tumors of different origins. - Conclusion Our data reveal that in the context of NK cells, IFNγ induces the resistance of tumor cells by the upregulation of classical and non-classical MHC-I. Moreover, we reveal insights into NK cell subset reactivity and propose a therapeutic strategy involving combinational monalizumab/lirilumab/DX9 treatment to fully restore the antitumor response across NK cell subsets.